Korelasi Manajemen Kepala Sekolah Penggerak dan Kinerja Guru Terhadap Kualitas Pembelajaran di SD GMIT Airnona 1 Kupang - Victryne Sofiani Seubelan (APOSTOLOS, 2023)
As a school with the status of a driving school, and led by a driving school principal as a school manager, and having teachers who are qualified educationally competent to be the main actors who play an important role in implementing classroom learning has not had an impact on the quality of learning achieved at SD GMIT Airnona 1 Kupang in 2 this past year (Year 2021-2022) as a driving school. This study uses correlational or correlation research methods. Based on the results of the simultaneous test through the F test, it shows that the calculated F value = 1,252 while the F table value is 4.74, it can be concluded that there is a positive correlation between the principal management variable (X1) and teacher performance (X2) on the quality of learning (Y ) at SD GMIT Airnona 1 Kupang. Therefore, as a driving school principal, he must have a driving force and must be able to apply good management so as to have a positive impact on all school members by creating a school climate that has a culture of quality, positive culture (discipline, ethics, effective communication), active participation and responsiveness. collaborative, safe and orderly. The management of human resources is closely related to the harmony between the working relationship of educators and educational staff as a capital for growing a learning climate to improve teacher performance and the expected quality of learning.